Comparative Study on Magnetic Characterization of Iron Sand from Several Locations in Central Java - Agus Yulianto; Satria Bijaksana; Waloejo Loeksmanto (Indonesian Journal of Physics, 2003)
Iron sand is a natural resource that is widely distributed in a number of places in Java. Although it is widely known, iron sand has not been utilized and exploited fully. To explore the possible utilizations of iron sand, we have carried out a survey on magnetic characters of iron sand from several locations in the north coast as well as in the south coast of Central Java. Samples in the form of raw iron sand were directly from the beach and were sun dried to reduce their water content before being taken to the laboratory. The mineralogy of the sample was observed using optical microscope as well as by X-ray diffraction method. Magnetic characterization was carried out by the measuring the magnetic susceptibility as well as the IRM (isothermal remanent magnetization) and its decay against demagnetization. The results show that the main magnetic mineral in iron sand from all location is magnetite (Fe3O4). Other magnetic minerals such as hematite and ilmenite are also present in the iron sand. The mass susceptibility varies from 1.01 × 10-4 m3/kg for sample from Munggangharjo to 3.34 × 10-4 m3/kg for sample from Bayuran. IRM analysis shows that the magnetite content varies considerably from one location to another one. Magnetite in the iron sand taken from locations in the northern part of Java tends to have smaller grain size compared to those from the southern part of Java.